Type and density of independent takeaway outlets: a geographical mapping study in a low socioeconomic ward, Manchester - Jennifer Blow; Sumaiya Patel; Ian G Davies; Rebecca Gregg (BMJ Open)
Objectives The socioeconomic disparity in childhood and early adult obesity prevalence has been well characterised. Takeaway outlets may cluster in lower socioeconomic areas and their proximity to schools is of concern. This study aimed to map takeaway food outlets, characterise takeaway types and their proximity to educational institutions within a low socioeconomic ward in Manchester.Design The Rusholme ward and a 2 km Euclidean buffer were included as the study area. Local authority Environmental Health data were used to map the takeaway outlets, using QGIS V.2.18.0 (OPENGIS.ch LLC, Einsiedeln, Switzerland). The types of takeaway outlets and major roads were included. Number of outlets within a 400 m Euclidean walking buffer of educational institutions were mapped.Setting Rusholme, Manchester, UK.Results Within the study area, 202 takeaway food outlets were identified and mapped as cluster points. Of these, 62.3% are located on major (A and B) roads, while the remaining outlets were located on minor roads. The majority (57.4%) of takeaway outlets sold similar items (fried chicken, burgers, pizzas, kebabs), with the remainder offering more diverse menus. Of the 53 schools, colleges and universities within the study area, 28 (52.8%) had 1–5 takeaway food outlets within 400 m, 9 (17.0%) had 6–10 outlets; 4 (7.5%) more than 11 outlets with 12 (22.6%) having zero outlets within 400 m.Conclusion Within this low socioeconomic area, there was a high concentration of takeaway food outlets, predominantly along major roads and in easy walking distance of educational establishments with the majority offering similar foods. In addition, a high proportion of these outlets were in easy walking distance of educational establishments. Public health policy needs to consider the implications of current takeaway food outlets and not just the proliferation of these outlets with current planning laws.